A Potential Link Between the Southern Ocean Warming and the South Indian Ocean Heat Balance. Issue 12 (3rd December 2020) - Yang, Lina; Murtugudde, Raghu; Zhou, Lei; Liang, Peng
Abstract: Using a suite of reanalysis products, model output, and observational data, the Southern Ocean (SO) is demonstrated to be undergoing a significant warming during recent decades, and this SO warming influences the subsurface heat redistribution in the South Indian Ocean (SIO) via two pathways. First, the increasing surface heat flux over the SO induces a poleward shift of the westerlies and the entire subtropical gyre. Consequently, waters on the equatorial side of the potential density troughs become cooler and those on the poleward side become warmer. The specific outcome is that the subsurface SIO is dominated by an extensive cooling, with a prominent deep‐reaching warming around 30°S‐20°S. Second, the SO warming signals are transmitted northward along isopycnal surfaces from around 40°S up to the tropical SIO through the meridional overturning circulation, modulating the decadal variability of the SIO. The present study highlights the role of the SO in regulating global ocean heat balance and facilitates a better understanding of the moderating effects of oceans on global climate. Plain Language Summary: The Indian Ocean is argued to modulate global climate through enhanced heat uptake since the 1960s. Nevertheless, the vertical distribution of ocean heat content is highly inhomogeneous, with the most striking feature being an extensive subsurface cooling which has been mainly attributed to the Pacific trade wind‐induced signal transmitted through the Indonesian Throughflow. Second, a hereto unexplained wedge of warming extending down to over 300 m depth is embedded around 30°S‐20°S. We find that the Southern Ocean (SO) warming modulates the subsurface heat redistribution in the South Indian Ocean (SIO) based on some reanalysis products, model simulations, and observations. As the surface heat flux over the SO increases, the westerlies shift poleward, resulting in a poleward displacement of the subtropical gyre. This results in a cooling on the equatorial side of the isopycnal troughs and a warming on the poleward side. Consequently, the subsurface SIO undergoes a relatively deep‐reaching warming in the south and an extensive cooling to the north. Besides, the SO signals are transmitted north to the SIO through the meridional overturning circulation at a relatively rapid decadal timescale. Therefore, the SO surface heat budget is crucial to the heat redistribution in the low‐latitude ocean basins. Key Points: The Southern Ocean (SO) surface heat flux is closely associated with the subsurface heat redistribution in the South Indian Ocean The SO warming‐induced poleward shift of the subtropical gyre is the main driver Local signals can further propagate northward through meridional overturning circulation from ∼40°S at decadal timescales